2023
DOI: 10.1111/apt.17523
|View full text |Cite
|
Sign up to set email alerts
|

Population‐attributable risk of modifiable lifestyle factors to hepatocellular carcinoma: The multi‐ethnic cohort

Abstract: Summary Background and Aims Lifestyle factors are well associated with risk of hepatocellular carcinoma (HCC). However, the impact of reducing adverse lifestyle behaviours on population‐level burden of HCC is uncertain. Methods We conducted prospective analysis of the population‐based multi‐ethnic cohort (MEC) with linkage to cancer registries. The association of lifestyle factors (smoking, alcohol, diet quality assessed by alternate Mediterranean diet score, coffee drinking, physical activity and body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…And the latest prospective analysis also confirmed that coffee drinking this lifestyle factors and the incidence of HCC is closely related to the lower risk. 13 The last review on this field was published by Kennedy's research team in 2017. 14 We decided to update the data in this field and synthesize information that includes the pathophysiological mechanisms, results of experimental and clinical studies, mechanisms of drug resistance and ways to overcome them, adverse effects of caffeine, recent patents in this field, and future developments.…”
Section: Introductionmentioning
confidence: 99%
“…And the latest prospective analysis also confirmed that coffee drinking this lifestyle factors and the incidence of HCC is closely related to the lower risk. 13 The last review on this field was published by Kennedy's research team in 2017. 14 We decided to update the data in this field and synthesize information that includes the pathophysiological mechanisms, results of experimental and clinical studies, mechanisms of drug resistance and ways to overcome them, adverse effects of caffeine, recent patents in this field, and future developments.…”
Section: Introductionmentioning
confidence: 99%